The impact of coaching communication styles and training programs on novice tennis player satisfaction: A case study from Indonesia - Zakaria, Mohammad Aldi; Nurrachmad, Limpad (CV Rezki Media, 2025)
Background: The satisfaction of beginner tennis players is often influenced by coaches' communication styles and the structure of training programs. Objectives: This study analyzed the effects of coaching communication style and training program design on player satisfaction at Club First Tennis. Methods: A quantitative, descriptive-associative approach was used with 50 beginner players in regular training sessions. Data were collected using a Likert-scale questionnaire covering coach communication style, training program design, and player satisfaction. Statistical analyses included validity and reliability tests, normality checks, and Spearman's rank correlation due to non-parametric data. Results: Results showed strong, significant relationships between coaching communication and player satisfaction (r = 0.615, p < 0.05), as well as between training programs and satisfaction (r = 0.620, p < 0.05). These findings indicate that supportive and adaptive communication and well-structured training enhance athlete satisfaction and engagement. Conclusions: The study highlights the importance of integrating effective communication and program planning in coaching beginner athletes. Future studies are encouraged to explore additional influencing factors such as intrinsic motivation or external support, and to involve larger sample sizes for broader generalizability.